ANTECEDENTS AND CONSEQUENCES OF CUSTOMER INTENTION TO ADOPT INTERNET BANKING THROUGH GAMIFICATION - Fransisca Angelina; Renny Risqiani; Amir Fikri (Universitas Trisakti, 2019)
Purpose – The purpose of this research is to analyze the influence of gamification in the use of internet banking on the intention of customers to adopt and recommend internet banking towards Compatibility, Innovativeness, Web Design, Web Characteristic, Performance Expectancy, Effort Expectancy . This research will help the Bank to measure the effect of gamification towards their customer to use Internet Banking. So they can innovate their Internet Banking system to be more fun and entertaining, so the customer will feel more enjoy to use and they will recommend to other people. Design/methodology/approach – 192 responses were collected from customers of internet banking user by using an online questionnaire. Using the convenience sampling approach. The collected data was analyzed using SEM with the help of PLS. Findings – The results indicate that intention to adopt internet banking is positively affected by Innovativeness, Web Design Performance Expectancy and Effort Expectancy . While compatibility and web characteristic doesn’t have a positive effect. The moderating effect of gamification suggested that the relationship between customer intention to adopt and customer intention to recommend will make the gamification effect become weak. Practical Implications – The research suggests that web designer and bank management should focus on the website design of the internet banking. Enjoyable internet banking website with reward and point system will help to improve user’s intention to adopt and intention to recommend internet banking with others. So the bank should make an innovative reward system for every transaction in internet banking. Originality/value – This research provide the technology acceptance construct and adding the game elements in technology perspective of internet banking as a moderating effect, to analyze the element effect towards intention to use and intention to recommend.